Curtailing The Security Challenge in Nigeria: Lessons From The Quranic Story Of Dhul-Qarnayn - Sulyman Muhammad Busayri; Abdulgafar Olawale Fahm (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2023)
The purpose of this paper is to examine the security challenge in contemporary Nigeria and to identify the lessons from the quranic story of Dhul Qarnayn as a model for addressing security issues in the country. This study is descriptive and qualitative. Selected examples of security issues in the QurÊ¾Än and early Islam, the quranic references to security in sura 18:83-101 and its connection to security challenges in Nigeria were reviewed, to identify a practical approach for curtailing security challenges to promote national development. Results show that Islam as a comprehensive religion, directly and indirectly, recommends various approaches towards mopping away the insecurity. The paper emphasizes successful experience of Dhul-Qarnayn as depicted in Q.18:83-101 is a sufficient idea in tackling the defacing occurrences of maiming, kidnapping, carting away of public properties, illegal protest, and the like.